Perancangan Sistem Informasi Pertanahan di PPATS Kecamatan Sukun Kota Malang - Hendy Rama Dhany; Meivi Kartikasari; Nira Radita (Prosiding SISFOTEK, 2021)
PPATS (Temporary Land Deed Officials) are officials involved in human legal needs in the land sector. PPATS has the task of making land deeds and land administration activities at the sub-district level. Currently in Sukun District in the process of delivering information regarding the processes and administrative requirements of inheritance letters, power of attorney and searching for land history files, it is still an offline information system, namely with an announcement board. In this study, a website-based information system will be created that will feature the process of managing inheritance letters, power of attorney, land history, monthly reports and also there are terms and conditions that can display letter formats or provisions for managing land certificates. The method used in this study is the waterfall method which includes the requirements, design, implementation, integration and testing, and operation and maintenance stages. The system is developed based on a website so that it can attract public interest. The blackbox testing method is used in the process of testing system functionality which is designed to find out whether it is as expected or not. Based on the results of these tests, it was concluded that with this system it could facilitate the process of obtaining inheritance and power of attorney, facilitate the process of recording land history, facilitate the monthly reporting process to the Office/OPD, and facilitate conveying information about land to the public.